Analisis Minat Kuliah Mahasiswa di STIE Gentiaras Bandar Lampung Melalui Media Periklanan - Jordan, Jordan; Kusumawati, Theresia Dhian (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2023)
The purpose of this study is to analyze students' lecture interest at STIE Gentiaras Bandar Lampung through advertising media. This type of study is causality associative study. The population in this study were all active students of STIE Gentiaras. The sampling technique in this study used the Proportional Stratified Random Sampling Technique with a total sample of 200 respondents. The data analysis method in this study used Simple Linear Regression Analysis. The result of data analysis in this study shows that there is an effect of advertising media towards students' lecture interest at STIE Gentiaras Bandar Lampung.